Immunohistochemical studies and fluorodeoxyglucose uptake on positron emission tomography in pharyngeal cancer for predicting radiotherapy‐based treatment outcomes. (14th November 2016) - Lin, Y.‐C.; Chen, R.‐Y.; Chen, S.‐W.; Hsieh, T.‐C.; Yen, K.‐Y.; Liang, J.‐A.; Yang, S.‐N.; Wang, Y.‐C.; Chen, Y.‐H.; Chow, N.‐H.; Kao, C.‐H.
Abstract : Objectives: This study correlated immunohistochemical studies with fluorodeoxyglucose (FDG) uptake on positron emission tomography–computed tomography (PET–CT) and identified prognostic factors for radiotherapy (RT)‐based treatment outcomes in patients with squamous cell carcinoma of the oropharynx and hypopharynx. Methods: Genomic data from pre‐treatment biopsy specimens ( Glut1, CAIX, VEGF, HIF‐1α, EGFR, Ki‐67, Bcl‐2, CLAUDIN‐4, YAP‐1, c‐Met and p16 ) of 7 6 patients were analysed using tissue microarrays. FDG uptake was evaluated using the maximum standardised uptake value (SUVmax), metabolic tumour volume (MTV) and total lesion glycolysis (TLG). Results: The overexpression of Glut1 positively associated with increased values of the SUVmax, MTV and TLG, whereas VEGF and HIF‐1α expression with the MTV and TLG, respectively. A VEGF immunoreactive score (IRS) >2 ( P = 0.001, hazard ratio [HR] = 3.94) and an MTV defined by an SUV of 2.5 (MTV2.5) >14.5 mL ( P = 0.004, HR = 3.31) were prognostic factors for low cause‐specific survival, whereas a VEGF IRS >2 ( P = 0.02, HR = 2.83) for low primary relapse‐free survival. Conclusion: The overexpression of Glut1, VEGF and HIF‐1α associated with increased FDG uptake. For patients with pharyngeal cancer requiring RT, the treatment outcome can be stratified by VEGF and MTV2.5.